Nepantleras. Spiritual artivism in Gloria E. Anzaldúa´s work - Bidaseca, Karina Andrea (Millcayac - Revista Digital de Ciencias Sociales, 2025)
This article addresses the last phase of Anzalduana's work, focusing on the concept of Napantla and nepantleras as the collective healing power of feminism. The drama of the exile of nomadism on a planetary scale, which I define as “Necro-frontiers,” is present in his mestizo thinking and in his embodied writing, challenging transdisciplinary approaches. La Llorona and the imperative Coyolxauhqui, as new identities, are mutations located between the human, non-human, and supernatural worlds, which connect at the suture point of the scars as traces of the common. The mutating forms of spiritual artivism are the legacy for the new feminist, Chicana, leather generations of the “mundo zurdo”.